Abundance and community structure of ammonia oxidizing bacteria and archaea in a Sweden boreal forest soil under 19-year fertilization and 12-year warming - Long, Xien; Chen, Chengrong; Xu, Zhihong; Linder, Sune; He, Jizheng (2012)
Boreal forests are considered to be more sensitive to global climate change compared with other terrestrial ecosystems, but the long-term impact of climate change and forest management on soil microbial functional diversity is not well understood. Ammonia-oxidizing bacteria (AOB) and archaea (AOA) are the most important players in nitrogen (N) cycling-associated processes in terrestrial ecosystems. This study investigated the separate and combined impacts of long-term soil warming and fertilization on soil AOB and AOA community structures and abundances in a Norway spruce stand in northern Sweden. The soil-warming experiment was established in the buffer zones of two irrigated plots (I) and complete nutrient solution plots (IL) since 1995. The warming treatment started in April each year by maintaining soil temperature on warmed plots at 5A degrees C above the temperature in unwarmed plots using heating cables. In August 2006, soil samples were collected from eight subplots for molecular analysis. The abundance of bacterial and archaeal amoA genes was determined by quantitative polymerase chain reaction. Similarly, total bacterial and archaeal population sizes have also been determined. The diversity of AOB and AOA was assessed by constructing amoA gene clone libraries, and different genotypes were screened with restriction fragment length polymorphism. Results showed that fertilization did not significantly affect the abundance of the bacterial amoA gene under either warming or non-warming conditions; however, warming decreased the abundance under fertilization treatments. No significant effects of fertilization and soil warming were observed on the number of thaumarchaeal amoA gene copies across all treatments. In this study, amoA gene abundance of AOB was significantly higher than that of AOA across all treatments. The community structure of both AOB and AOA was strongly influenced by fertilization. For bacterial amoA genes, Nitrosospira cluster 2 was present across all treatments, but the only genotype was ...